Pengaruh Komisaris Independen, Leverage, dan Financial Distress terhadap Manajemen Laba : Studi Empiris pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2022 - Musdjalifah, Sabnah; Kalbuana, Nawang; Wangsih, Ingkak Chintya (Goodwood Akuntansi dan Auditing Reviu, 2024)
Purpose: This study analyzes the impact of independent commissioners, leverage, and financial distress on earnings management in the transportation and logistics sectors listed on the Indonesia Stock Exchange during the period 2018 – 2022. Research Methodology: The method employed was quantitative research, with the dependent variable being earnings management. The independent variables examined include independent commissioners, leverage, and financial distress. The study selected 85 companies using the purposive sampling method. Data analysis was conducted by testing the classical assumptions and hypotheses using multiple regression. Results: The findings indicate that independent commissioners do not influence earnings management, while leverage and financial distress have a significant negative impact on earnings management. Limitations: The study only utilizes 3 (three) independent variables: independent commissioners, leverage, and financial distress. The period considered was only 5 (five) years, from 2018 to 2022. This study focuses exclusively on the transportation and logistics sectors listed on the Indonesian Stock Exchange (IDX). Contribution: For investors, it is hoped that it can provide information to be more aler when reading or analyzing financial reports and for company management, it is hoped that it will be useful for internal parties in the company so that it can be used a basis for argumentation when making policy decisions.